Principal quality management in improving teacher performance in elementary schools: Case study of sdn babakan karamat and sdn tegal pari - Mita Martinah; Sobari Sobari (At Turots: Jurnal Pendidikan Islam, 2025)
In the realm of education, the principal's role significantly impacts teacher quality. As a leader, the principal bears the responsibility for enhancing educational standards within their school. However, it is undeniable that some principals struggle to fulfill their roles effectively. Some remain entangled in administrative tasks, limiting their capacity to adequately focus on teacher development, which negatively affects educational quality. This study aims to investigate the principal's role in improving teacher performance. Employing a descriptive qualitative approach with a multi-site research design, the study was conducted at two locations. Data collected were analyzed through qualitative descriptive analysis to identify factors influencing strategic management, the principal's role, and the impact of implementation on teacher performance at SDN Babakan Karamat and SDN Tegal Pari. Principals at these schools strive to foster a supportive environment for teacher professional development. This approach is expected to significantly improve teaching quality, positively influencing student learning outcomes. The primary finding of this study reveals that meticulous planning and the implementation of continuous training programs are effective in enhancing teacher professional skills. Furthermore, the collaborative strategies employed between principals, teachers, and other stakeholders support the sustained improvement of educational quality at SDN Babakan Karamat and SDN Tegal Pari.